Malnutrition During Pregnancy Among Child Bearing Mothers in Mbaitolu of Imo State, Nigeria - Opara, Jacinta A.; Ebuoluwa, Adebola Helen; Oguzor, Nkasiobi Silas; Sodienye, A. Abere (Mediterranean Journal of Social Sciences, 2011)
This study examines consequences of malnutrition during pregnancy among child bearing mothers in Mbaitolu LocalGovernment Area of Imo State, Nigeria. The study also identifies the cause of consequences among child bearing mothers. Thepopulation of the study comprised 200 child bearing mothers who registered with the Primary Health Centres. The wholepopulation was used as sample. Hence, there was no sampling technique used. A questionnaire was used for data collection.Data collected were analyzed applying frequency counts and mean statistic. Findings revealed that abortion and prematuredelivery can be as a result of malnutrition. The finding of the study also revealed that malnutrition in pregnancy result in offspringwith low birth weight and high risk of prenatal mortality. The study of the finding further showed that socio economic factors,cultural beliefs are some of the causes of malnutrition in pregnant mothers. Based on the findings the followingrecommendations were made. That adult educators, midwifes, medical doctors should assist in educating the child bearingmothers on how to eat balanced diet. This will help to reduce problems of malnutrition in childbearing mothers.